2022
DOI: 10.3390/fermentation8100478
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Solid-State Fermentation of Okara and Copra Meal by Probiotics with Non-Starch Polysaccharide Enzymes and Its Effects on the Growth Performance and Ileal Microbiota in Broilers

Abstract: With the global shortage of feed ingredients, the use of agricultural by-products has become an alternative to animal feed. Okara, a by-product of soymilk and tofu processing, is high in nutrients but contains non-starch polysaccharides (NSP) and has a high-water content, which are disadvantages in animal feed. Herein, we mixed okara and copra meal (CM) with probiotics (Lactobacillus species and Clostridium butyricum) and NSP enzymes (NSPases) for solid-state fermentation (SSF) to enhance okara feed value; the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…Moreover, the insufficient water content in the substrate limits the enzyme's activity. Recently, Hsiao et al [28] have proven that only after 48 h, sugar reduction increased through the action of carbohydrates, which provided the microorganisms to continue producing lactic acid. On the other hand, in the current study, glucose and fructose levels were significantly higher in products where α-amylase, endo 1,4-β-xylanase, and endo-1,3(4) β-glucanase were individually used, which can be a result of partial carbohydrate changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the insufficient water content in the substrate limits the enzyme's activity. Recently, Hsiao et al [28] have proven that only after 48 h, sugar reduction increased through the action of carbohydrates, which provided the microorganisms to continue producing lactic acid. On the other hand, in the current study, glucose and fructose levels were significantly higher in products where α-amylase, endo 1,4-β-xylanase, and endo-1,3(4) β-glucanase were individually used, which can be a result of partial carbohydrate changes.…”
Section: Discussionmentioning
confidence: 99%
“…The fermentation technique of high-protein feed using various microorganisms, such as bacteria or yeast, has been frequently studied and utilized in formulated animal mixtures in recent years [7,8,14,15]. To date, there are limited data on the evaluation of directly fermented feed with exogenous enzymes in animal nutrition [10,28] because most fermentation mechanisms that reduce antinutrient contents are uncharacterized [38], except for phytate [39]. Many studies have shown that high dietary inclusion of raffinose family sugars in feeds containing high levels of crude fiber and other antinutrients could lead to decreased feed intake and BW gains and increased mortality [9,20].…”
Section: Discussionmentioning
confidence: 99%
“…In another attempt, the agricultural waste hull-less barley and corn straw were used to prepare feed from Lactobacillus plantarum with or without molasses or fibrolytic enzymes ( Kim et al, 2012 ; Hajimohammadi et al, 2020 ; Li et al, 2020 ; Hsiao et al, 2022 ). The use of Lactobacillus plantarum in the silos significantly reduced the pH and the NH3-N, acetic acid, and butyric acid concentrations in the prepared silages compared to those in the control group.…”
Section: Fermented Citrus Residue As a Nutritious Biofeedmentioning
confidence: 99%
“…Lactic acid bacteria further decreased (p<0.05) the ratios of acid detergent fiber to acid detergent lignin ( ADL ), neutral cellulose to ADL, and hemicellulose to ADL. By adopting the idea of lactic acid fermentation to prepare high-quality sustainable foods, several other attempts have been made to improve the nutritional value of many plants and plant wastes, such as sesame ( Hajimohammadi et al, 2020 ; Li et al, 2020 ), soybean ( Kim et al, 2012 ; Li et al, 2020 ), Artemisia princeps ( Kim et al, 2012 ), okara and Copra ( Hsiao et al, 2022 ), mulberry leaf ( Ding et al, 2021 ), ginkgo leaf ( Zhang et al, 2015 ), wheat, oats, and barley grains ( Yaşar et al, 2016 ). These efforts have yielded successful results, with the improved nutritional value of end products effectively utilized in animal production.…”
Section: Fermented Citrus Residue As a Nutritious Biofeedmentioning
confidence: 99%
“…However, scarce information exists to improve the quality and use of coconut meat waste in poultry diets. Numerous studies have suggested that the results of the study showed that inclusion of mannanase enzyme and probiotics in diets containing high Non-Starch Polysaccharides (NSP) such as mannan and galactomannan could improve growth performance (Khanongnuch et al, 2006;Sundu et al, 2006;Hsiao et al, 2022), gut histomorphology (Awad et al, 2009;Rahimi et al, 2009;Aliakbarpour et al, 2012;Mikulski et al, 2012) of broilers.…”
Section: Introductionmentioning
confidence: 99%